MORTALITY FROM LAND TRANSPORT ACCIDENTS: A COMPARATIVE ANALYSIS - Marília Angelina Ferreira Papa; Danielle Wisnieswski; Kelly Cristina Inoue; Carlos Alexandre Molena-Fernandes; Yolanda Dora Martinez Évora; Laura Misue Matsuda (Universidade Federal do Paraná, 2014)
This is an epidemiological, descriptive, comparative study whose objective was to compare the mortality from Land Transport Accidents in the cohorts: 2006/2007 and 2009/2010, in Maringá in the Brazilian State of Paraná. Inferential statistics were undertaken (Chi-squred test) using the Statistica 8.0® software. It was observed that Land Traffic Accidents are the main causes of mortality from external causes - the local coefficient of mortality was 34.98%, above the national rate, principally among pedestrians, motorcyclists and men between 20 and 39 years old. And that in the comparison of the differences of the coefficient of mortality between the cohorts, there was an increase of 26.4%. It is concluded that there was, in the city, an increase of the coefficient of mortality from Land Transport Accidents. Thus, further investment is suggested in traffic education programs; inspections; and in studies evaluating the impact of the measure restricting the use of alcohol and driving in the traffic.